KNOWLEDGE AND PRACTICE REGARDING FOOT CARE AMONG TYPE 2 DIABETES MELLITUS PATIENTS AT A TERTIARY CARE HOSPITAL IN COASTAL SOUTH INDIA - BB, DARSHAN; UNNIKRISHNAN, BHASKARAN; KULKARNI, VAMAN; THAPAR, REKHA; MITHRA, PRASANNA; KUMAR, NITHIN; HOLLA, RAMESH; KUMAR, AVINASH; JATANA, VAISHNAVI; KOLLURU, SAHITI; PHOGAT, VAISHALI; NAMBIAR, ARTHI; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was designed to assess the knowledge and practice among diabetic patients in a tertiary care hospital regarding diabetic foot care. Methods: A cross-sectional study was conducted in government district hospital of Mangalore in the month of January 2014. A pre-designed semistructured questionnaire was used to collect the information pertaining to the knowledge and practices of the diabetic patients regarding foot care. The collected data were analyzed using Statistical Packages for Social Sciences version 11.5. The results obtained were expressed in proportions. Results: A total of 133 subjects were assessed regarding their knowledge and practice regarding diabetic foot care. Around three-fourth (75.2%) of participants had adequate knowledge. More than half (55.5%) of the subjects had adequate practice. No significant association was found between study variables such as gender, socioeconomic status, and education status with awareness regarding diabetic foot care in the present study (p>0.05). Gender, socioeconomic, and educational statuses were found to be significantly associated with diabetic foot care practices. Conclusion: The gap between knowledge and practice regarding self-care among diabetic patients can be bridged by providing continuous health education by the health workers. Foot care should be promoted at all available opportunities whenever the patient comes in contact with the health system. Keywords: Mangalore, Foot care, Diabetes.